Risk Assessment Strategy for Corrosion Under Insulation of Nano Technology Insulation on Geothermal Pipeline - Andiani Setia Wardani; Ekha Panji Syuryana; Sutarno Sutarno; Basuki Nugroho; Gian Ganjar Zatnika; Gusti Verhan Pratama; Moch. Salman Fadillah Suardana (Journal of Mechanical Engineering, Science, and Innovation, 2022)
Pipelines are important in geothermal and most of the pipe materials are carbon steel insulated. Pipe insulation that is often used in general is prone to wetness, heat loss, and corrosion. Corrosion is a problem especially Corrosion Under Insulation (CUI). This corrosion results in pipeline leakage. The selection of nano-tech insulation is a way to overcome CUI and extend service life pipe usage. The study used JIS S45C 1Ã—1 cm insulated with nanotechnology by dripping 3.5% NaCl for 3 days and room temperature. Corrosion rate, metallography, and roughness were sought so that the corrosion rate was 0.0894 mpy, the average surface area corroded was 2.22 mmÂ². The original roughness value is 0.528 - 1.725 mm. This shows that the nano- tech insulator minimizes the formation of CUI on the specimen.